An application of multi-objective transportation problem in type-2 Fermatean fuzzy number incorporating the RS-MABAC technique - P. Anukokila; R. Nisanthini; B. Radhakrishnan (Franklin Open)
This study describes two decision making problems in trapezoidal type-2 Fermatean fuzzy numbers. Firstly, to address multi-criteria decision-making problem, we provide a hybrid rank sum and multi-attributive border approximation area comparison approach that ranks alternatives from best to worst contingent upon decision makers’ preferences. The second phase is to define a multi-objective transportation problem where the model is reduced to a single objective problem using the data envelopment analysis technique. The simplified single-objective issue is then solved using LINGO-18.0, producing a collection of optimal solutions. Lastly, the suggested method is used to address a medical supply transportation problem, and the outcomes are compared and discussed.